Beirut rules : the murder of a CIA station chief and Hezbollah's war against America and the West - Burton, Fred, 1958- (Berkley, 2018)
From the New York Times bestselling coauthors of Under Fire: The Untold Story of the Attack in Benghazi comes the riveting true story of the kidnapping and murder of CIA station chief William Buckley and the bloody beginning of the CIA's endless war against Islamic radicalism. On April 18, 1983, a van rigged with two thousand pounds of heavy explosives broke through the security perimeter of the American embassy in Lebanon and exploded, killing sixty-three people and decimating intelligence operations throughout the Middle East. Only one man inside the CIA possessed the courage and skills to rebuild the networks destroyed in the blast: William Buckley. Assigned as the new Beirut station chief, Buckley arrived in the war-torn city to find a CIA station in tatters and an intelligence playing field unlike any other in the world; the veteran of the Cold War would now be learning Beirut rules. A field operative at heart, he delved into Beirut's darkest corners, developing new sources and handling assets. Then, on October 23, a US Marine Corps barracks was destroyed in a plot masterminded by a young terrorist named Imad Mughniyeh. But even as President Reagan vowed revenge, Mughniyeh eyed a new target: Buckley. Beirut Rules is the pulse-by-pulse account of Buckley's abduction, torture, and murder at the hands of Hezbollah terrorists. Drawing on never-before-seen US government documents, as well as interviews with Buckley's former coworkers, friends, and family, Fred Burton and Samuel M. Katz reveal how the pursuit to find Buckley in the wake of his kidnapping ignited a war against terror that continues to shape the Middle East to this day.